Freely Deformable Electrochromic Fabric Devices Exhibiting Durable Chromatic Switching and All-Around Stability. Issue 2 (1st February 2022) - Eom, Yu Seon; Pal, Raksha; Pande, Gaurav K.; Park, Jong S.
Abstract : Electrochromic devices (ECDs) show reversible color changes on applying external voltages by electrochemical redox reactions. Most ECDs are fabricated using ITO-coated electrodes on glass substrates. With a growing interest in wearable devices, many attempts have been made concerning flexible ECDs. Compared to the conventional devices, the ECDs fabricated on the textile substrate feature highly conformal and curvilinear properties similar to inherent textile aspects. In line with the demand, this study presents the freely deformable and highly durable electrochromic fabric devices (ECFDs) prepared by the spray-coating process. The ECFDs are constructed using a layer-by-layer structure on polyester fabric, consisting of electrodes, electrochromic, electrolyte, and protective layers. Conducting electrodes are designed with the mixture of silver nanowire and PEDOT:PSS, and, on top of it, viologen functionalized polyhedral oligomeric silsesquioxane is subsequently stacked. The additional electrolyte layer is placed for surface hardening and ion transporting purposes. The protection is formed in the outer layer, providing remarkable waterproofness and laundry fastness. The prepared ECFDs reveal reversible and repeated electrochromic performances, along with bending and twisting stability, waterproofness, and washing fastness. The current approach demonstrates the feasibility of color-changing textiles for real-life applications.